Cyclical transmission of pathogenic Trypanosoma species by gamma-irradiated sterile male Glossina morsitans morsitans - Moloo, S.K. (Cambridge University Press, 1982)
Investigations were conducted on the infection rates and transmission charecteristics of sterile male Glossina morsitans morsitans for Trypanosoma vivax, T. congolense and T. brucei. Pupae were irradiated after the first flush of female emergences with 7, 10 or 13 krad. in a 137caesium radiation source under ambient conditions. The emergent males were fed on a T. viuax-infected goat at peak parasitaemia. They were subsequently mated at 8 days old with 3-day-old normal, virgin females. A batch of sexually fertile males which had been infected as tenerals on the goat at the same time were similarly mated to serve as controls. All the tsetse were maintained on rabbits' ears; the survival and reproductive performance were monitored for seven age-group periods of 9 days each. The sterility rates of the males were 73, 91 and 98% for the 7, 10 and 13 krad. doses of radiation; the percentage of T. vivax infection rates were 78·3, 82·3 and 74·4, respectively. For the control males, the fecundity of the mated females was 90% and the infection rate was 75·7%. In all other experiments, the 10 krad. dose was selected since both the survival and the sterility of the irradiated males were good. The T. vivax-challenged cows and goats died with symptoms of anaemia. There was no difference in the transmission characteristics between sterile and fertile vectors. There was also no significant difference between the sterile and normal males in the infection rates and the transmission frequency of T. congolense and T. brucei to cattle, goats and mice. These results indicate that release of sterile male tsetse in tsetse control programmes will potentially increase the trypanosomiasis risk in the affected area. Consideration must therefore be given to integrating adequate surveillance and chemotherapeutic measures for protection of man and his domestic livestock in the region during the period of such tsetse control campaigns.